Glutathione-dependent system of antioxidant protection in the animal’s organism under effect of electromagnetic radiation - Tomashevska, L.A.; Kravchun, T.Ye. (Environment & Health, 2018)
Objective: We investigated the state of the glutathione-dependent system of antioxidant protection under exposure of electromagnetic radiation in the experiment.Materials and methods: The investigations were carried out under conditions of 4-month chronic experiment on white non-pure rats which were divided into groups according to the current EMR intensity of 900 MHz (10 μW / cm2, 10 μW / cm2, 10 μW / cm2). We used blood, liver, and brain as a biological material for the investigations.Results: Strengthening of lipid peroxidation processes in the blood, liver, and brain tissue was established. Those changes were manifested depending on the level of the intensity of EMR and the time of exposure. An increase in the activity of antioxidant glutathione-dependent enzymes – glutathione peroxidase, glutathione reductase, glutathione transferase, as well as a decrease in the level of reduced glutathione, manifested at the increase of intensity (100 and 1000 μW / cm2) of EMR and time (3-4 months of irradiation), were detected. The cooperative antioxidant activity of glutathione and enzymes is insufficient to neutralize the lipid peroxidation process initiated by EMR. Induction of lipid peroxidation and activation of glutathione enzymes indicate a change in pro- and antioxidant balance, a violation of this balance characterizes a degree of stress on the adaptive capabilities of the organism under the influence of EMR.Conclusions: The identified shifts in the ratio of the intensity of lipid peroxidation and the activity of enzymes of glutathione system as a sensitive biomarker of influence can have prognostic significance for the substantiation of the safe EMR regulations.
Keywords: electromagnetic radiation; antioxidant activity; glutathione-dependent enzymes